Preparation of Visible Light Responsive Carbon Doped Titania Catalyst via Simple Sol-Gel Method - Zhang, J.; Wang, Y.J.; Hu, S.Z. (Asian Journal of Chemistry, 2014)
Sol-gel method was used to prepare carbon-doped TiO2 nanoparticles and characterized by XPS, XRD, Photoluminescence and UV-visible spectra. UV-visible diffuse reflectance spectra showed that carbon-doped TiO2 exhibited an improved absorption in the visible light range. The visible light photocatalytic activity of carbon-doped TiO2 was ascribed to the presence of oxygen vacancy state between the valence band and conduction band because of the formation of Ti3+ species in the prepared carbon-doped TiO2. The catalyst calcined at 500 °C showed the highest photocatalytic activity in the degradation of methylene blue under visible light irradiation. The possible mechanism was presented.